Prognostic Factors in Pediatric Early Liver Retransplantation. Issue 4 (4th March 2020) - Cañon Reyes, Isabel; Halac, Esteban; Aredes, Diego; Lauferman, Leandro; Cervio, Guillermo; Dip, Marcelo; Minetto, Julia; Reijenstein, Hayellen; Meza, Veronica; Gole, Maria; Jacobo Dillon, Agustina; Imventarza, Oscar
Abstract : The most common indications for early liver retransplantation (eRe‐LT) are vascular complications and primary nonfunction (PNF). These patients are usually in a critical clinical condition that can affect their chances of survival. In fact, the survival of these patients is usually lower compared with the patients undergoing a first transplant. To the best of our knowledge, no specific series of pediatric patients undergoing eRe‐LT has been published to date. Therefore, the aim of this study is to report the results of eRe‐LT and to analyze factors potentially related to success or failure. Our work is of a retrospective cohort study of patients who underwent eRe‐LT at the Juan P. Garrahan Pediatric Hospital of Buenos Aires, Argentina, between May 1995 and December 2018 (n = 60). Re‐LT was considered early when performed ≤30 days after the previous LT. A total of 40 (66.7%) patients were enrolled due to vascular causes and 20 (33.3%) were enrolled because of PNF. Of all the relisted patients, 36 underwent eRe‐LT, 14 died on the waiting list, and 10 recovered without eRe‐LT. A total of 23 (63.9%) patients died after eRe‐LT, most of them due to infection‐related complications. Survival rates at 1 and 5 years were 42.4% and 33.9%, respectively. On univariate logistic regression analysis, Pediatric End‐Stage Liver Disease (PELD)/Model for End‐Stage Liver Disease (MELD) scores, transplant era, and advanced life support at eRe‐LT were found to be related to 60‐day mortality. However, on multivariate analysis, era (odds ratio [OR], 9.3; 95% confidence interval [CI], 1.19‐72.35; P  = 0.033) and PELD/MELD scores (OR, 1.07; 95% CI, 1‐1.14; P  = 0.036) were significantly associated with 60‐day patient mortality. This study found that the level of acuity before retransplant, measured by the requirement of advanced life support and the PELD/MELD score at eRe‐LT, was significantly associated with the chances of post–eRe‐LT patient survival.